E-learning technologies and evidence-based assessment approaches - Spratt, Christine; Lajbcygier, Paul (Hershey, PA : Information Science Reference)
"This book aims to provide readers with a variety of contemporary solutions to identified educational problems of practice related to the assessment of student learning in e-learning environments"--Provided by publisher